Scientific basis of design structures plaster solutions - Paruta, Valentyn; Gnyp, Olha; Lavreniuk, Leonid; Bachinsky Vyacheslav, Bachinsky Vyacheslav; Grynyova, Iryna (Academic journal Industrial Machine Building Civil Engineering, 2019)
High-rise construction volume increase and new wall materials use require changing the approach to the design of plastermortar compositions. The analysis has showed that it is possible to reduce the number of cracks in the plaster coating by increasingthe water holding capacity of the mortar mixture. To optimize the prescription parameters of the mortar mixture, thefive-factor experiment with fine aggregate and the filler with a low modulus of elasticity, disperse polymeric powders andcellulose ethers, a polymer fiber for microdispersed reinforcement has been used. The obtained data indicate that the proposedapproach enables to obtain plaster mortars with physic mechanical characteristics that provide optimal working conditions“masonry - plaster coatings”.
Keywords: plaster solutions; new basic principles for designing their compositions